A Excel Based Software Solution for Administrative and Educational Tasks in Higher Education Institutions - Balkash, Abdulmajied Ali; Rashid, Abdulnaser; Alrahal, Debo (Journal of Global Economy, Business and Finance, 2026)
This article describes the development and implementation of a comprehensive computer program designed to reduce the administrative workload and prepare reports by the perpetual controller for submission to college administration. The paper emphasizes the great burden that falls on the administration conferences. The developed program provides, provides reports that are easy, accurate, and efficient. The researcher relied on Excel techniques and used many advanced Excel functions to manage data and create error-free reports. The article discusses the program's input and output mechanisms, its security features, and its practical application at Qassim University, highlighting its effectiveness in simplifying administrative duties while enhancing report accuracy. to schedule lectures without conflicts, as well as to Select appropriate halls for lectures, public meetings, or conferences.